2020
DOI: 10.1101/2020.11.03.366971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitrate inhibits nodule organogenesis through inhibition of cytokinin biosynthesis inLotus japonicus

Abstract: Legumes balance nitrogen acquisition from soil nitrate with symbiotic nitrogen fixation. Nitrogen fixation requires establishment of a new organ, which is a cytokinin dependent developmental process in the root. We found cytokinin biosynthesis is a central integrator, balancing nitrate signalling with symbiotic acquired nitrogen. Low nitrate conditions provide a permissive state for induction of cytokinin by symbiotic signalling and thus nodule development. In contrast, high nitrate is inhibitory to cytokinin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Cytokinin levels were strongly induced by Phtheirospermum infection (Fig.4), consistent with previous findings (Spallek et al, 2017), but we found no evidence that nitrate itself induced cytokinin levels or induced cytokinin response in Phtheirospermum . Notably, nitrate treatment of Lotus japonicus inhibited cytokinin biosynthesis, reduced cytokinin levels and reduced nodule formation (Lin et al, 2020). In Phtheirospermum , nitrate treatment also reduced cytokinin levels and cytokinin response compared to water treatment (Fig.4B, Fig.S4).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokinin levels were strongly induced by Phtheirospermum infection (Fig.4), consistent with previous findings (Spallek et al, 2017), but we found no evidence that nitrate itself induced cytokinin levels or induced cytokinin response in Phtheirospermum . Notably, nitrate treatment of Lotus japonicus inhibited cytokinin biosynthesis, reduced cytokinin levels and reduced nodule formation (Lin et al, 2020). In Phtheirospermum , nitrate treatment also reduced cytokinin levels and cytokinin response compared to water treatment (Fig.4B, Fig.S4).…”
Section: Discussionmentioning
confidence: 99%